The influence of internal resources and entrepreneurial orientation on the performance satisfaction of batik firms in Malaysia / Dewi Izzwi Abddul Manan - Abddul Manan, Dewi Izzwi (Institute of Graduate Studies, UiTM, 2013)
Malaysian batik industry is one of the oldest industries as it has been existed in Malaysia since 1921. The industry produces variety of batik-based products including textiles, ready-made garments and household goods. Through out of its existence, batik industry has contributed to Malaysian economy by creating business and job opportunities, and also supporting tourism industry. As an old industry, it is fascinating to learn how firms in that industry able to perform. Unfortunately, from academic research point of view, the industry was seen to be very much neglected. Hence, this research is undertaken to study the influence of internal resources and entrepreneurial orientation towards batik firm performance. Explicitly, this research’s objectives were to identify whether there are positive relationships between reputation, human capital, culture and marketing capability with batik firms’ performance satisfaction. This research also examined the moderating effect of entrepreneurial orientation’s dimension on the relationship between resources and performance satisfaction…